(untitled) (Journal of Pharmaceutical Negative Results, 2023)
Background :Anemia and diabetic foot ulcers are two common side effects of diabetes. We set out to collect information on the prevalence of anaemia in people with and without diabetic foot ulcers (DFUs) who were of comparable ages and sexes to investigate the association between anemia and diabetic foot ulcers (DFUs) in patients with diabetes. A total of 371 patients with diabetes and DFUs from a tarrtery care hospital of kpk , pakistan . Method The study conducted in department of Diabetes and endocrinology Hayatabad Medical Complex Peshawar from October 2019 to October 2021 A total of 371 patients with diabetes were included in the study. Data were collected from medical records regarding demographics (age, gender, body mass index, etc.), clinical characteristics (hemoglobin [Hb] level, anemia, etc.), and DFUs. Anemia was defined as a Hb level less than 13.0 g/dl for men and 12.0 g/dl for women. DFUs were defined as any ulcer on the foot that was present or had been present in the previous 12 months. Results Out Of the 371 patients included in the study, 120 (32.4%) had anemia. The results showed that patients with anemia were more likely to have DFUs than those without anemia (odds ratio [OR] = 2.48; 95% confidence interval [CI], 1.79- 3.45). Additionally, an inverse association was found between Hb level and DFUs (OR = 0.99; 95% CI, 0.99-0.99). Other potential risk factors for DFUs, such as age, gender, body mass index, and duration of diabetes, were not significantly associated with DFUs. Conclusion This Single-center study demonstrated a strong association between anemia and DFUs in patients with diabetes. The findings suggest that screening and timely treatment of anemia should be considered in the prevention and management of DFUs.